The Effect of Using Educational Videos in Digital Marketing Education and Training Programs on Improving the Marketing Knowledge of Members of Village -Owned Enterprises (BUMDeS) Bina Sejahtera Kedungadem Village Bojonegoro Regency - Lia Pebriana Puspitasari; Sri Sumaryati; Sudiyanto Sudiyanto (Social, Humanities, and Educational Studies (SHES): Conference Series, 2023)
The rapid development of digital technology requires every BUMDes organization to be able to improve the competence of its members regarding digital marketing. One way is to increase marketing knowledge through digital marketing education and training using educational videos. This study aims to determine the effect of using educational videos in digital mark eting education and training on increasing the marketing knowledge of BUMDes Bina Sejahtera members of Kedungadem Village. This study used a pre-experiment design of one group pre-test post-test design. The population of this study were 50 BUMDes members. The sample of this study was 44 BUMDesmembersselectedbyclusterrandomsampling. Theresearchdatawascollectedusing questionnaires and paired t-test (α≤0.005). The results showed that 34 BUMDes members (77.2%) had a low level of knowledge before being given digital marketing education and training using educational videos and increased to (77.3%) after being given digital marketing education and training using educational videos. The paired t-test results show that there is an effect of using educational video media in digital marketing education and training on increasing the marketing knowledge of BUMDes members (P=0,00). Future research can conduct research by providing a control group and using other comparison methods.